Reinterpretasi Hadis Larangan Kepemimpinan Perempuan: Telaah Hermeneutika Nasr Hamid Abu Zayd - Mawarda, Lisa; Masruhan, Masruhan (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
This study focuses on reinterpreting the meaning of hadiths on female leadership and the implications of Nasr Hamid Abu Zayd's hermeneutics on contextual hadiths. This study is a qualitative study using library research and Nasr Hamid Abu Zayd's hermeneutics approach. The final results obtained from this study are, first, the interpretation of the Qur'an and hadith as texts cannot only be understood through linguistic analysis, but also the historical context at the time the Qur'an and hadith were revealed because the texts have historical dimensions. Second, Abu Zayd explains that in interpreting texts, a mufassir must be able to explain three main concepts, namely meaning (dalalah), significance (magza), and maksut 'anhu (unspoken dimensions). Third, based on the application of hermeneutics, it is concluded that the meaning of the hadith is that the prohibition is specific to the conditions of society at the time of the Prophet. Its significance affirms that leadership requires capacity, not gender, and that Islam must be understood in the spirit of justice and the benefit of the people. Meanwhile, the implicit purpose of the hadith (maqsūd 'anhu) points to the need for stability and social justice that can be achieved by anyone, male or female, as long as they meet the criteria for leadership.